Læring gennem mad og måltider i grundskolen Teori og praksis fra Danmark, Sverige og Norge - Ruge, Dorte (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
How are school meals organized in the Scandinavian countries? And in what ways can new pedagogical practice lead to better school meal programs for students and a better understanding of the importance, for health and sustainable development, of the food offered through schools? Learning Through Food and Meals in Primary School takes a look at school meal programs in Denmark, Sweden and Norway with the objective of providing educators and teacher-education students an understanding of school meals from public health and nutritional perspectives, as well as a sense of the potential for teaching through school meals. The book is written in Danish, Swedish and Norwegian, and is structured in three parts, presenting new research from each of the three countries. Thematically, the chapters range from studies of different school meal initiatives to analyses of the social, democratic, and pedagogical significance of school meals. Through the different contributions, the book presents both experiences of how teaching through food can be done in a practical sense and an argument for its importance in an overall pedagogical and didactic perspective. The book will be relevant for anyone who is interested in food and meals served in primary schools, such as teachers, researchers, politicians and school administrators. The authors include researchers, educators and primary school administrators. Learning Through Food and Meals in Primary School has been edited by Dorte Ruge (UCL University College, Denmark), Frøydis Nordgård Vik (University of Agder, Norway), and Johanna Björklund and Sara Frödén (Örebro University, Sweden). The anthology has been made possible with the support of Nordplus Horisontal, project LEARNFOOD. The illustrations on the cover of the book are by Elisabeth Werngren (Sweden) and Marie Madsen (Denmark).